Design, microstructure and mechanical characterization of Ti6Al4V reinforcing elements for cement composites with fractal architecture. (15th June 2019) - Farina, Ilenia; Goodall, Russell; Hernández-Nava, Everth; di Filippo, Andrea; Colangelo, Francesco; Fraternali, Fernando
Abstract: This paper presents a study on the design, and microstructural and mechanical characterization of additively manufactured reinforcing elements for composite materials exhibiting fractal geometry, with a focus on the flexural reinforcement of cement-matrix composites. The examined elements are manufactured via an additive process, electron beam melting, from the Ti6Al4V titanium alloy, using a Koch curve construction ruled by three complexity parameters. Koch fibers and meshes are designed, additively manufactured and experimentally tested, through the use of the proposed fractal design procedure. Laser scanning tests illustrate the correspondence between the CAD objects and the additively manufactured samples. The experimental characterization of the surface properties of the Koch fibers is conducted through optical microscopy and contact angle tests, while their mechanical performance is analyzed through Vickers hardness and bending tests on a fiber-reinforced reinforced mortar. The given mechanical tests highlight that reinforcing fibers with fractal architecture significantly enhance the first crack strength and the residual loading capacity of cement mortar specimens subject to three-point bending tests. This is due to the relevant interlocking mechanisms acting at the interface between the matrix and the ribs of such reinforcing elements, which delay the macroscopic cracking of the mortar. Graphical abstract: Unlabelled Image Highlights: A general procedure for the design of reinforcing elements with fractal architecture is presented. Physical models of Koch fibers and meshes are additively manufactured through electron beam melting. The accuracy of the reproduction of fractal geometries through additive manufacturing is investigated. The mix design and the mechanical characterization of a cement mortar to be reinforced with Koch fibers are given. Bending tests on mortar specimens reinforced with Koch fibers show marked matrix-rebar interlocking effects.